PEGylation and folic-acid functionalization of cationic lipoplexes—Improved nucleic acid transfer into cancer cells - Hoffmann, Marco; Gerlach, Sven; Hoffmann, Christina; Richter, Nathalie; Hersch, Nils; Csiszár, Agnes; Merkel, Rudolf; Hoffmann, Bernd (Frontiers in Bioengineering and Biotechnology, 2022)
Efficient and reliable transfer of nucleic acids for therapy applications is a major challenge. Stabilization of lipo- and polyplexes has already been successfully achieved by PEGylation. This modification reduces the interaction with serum proteins and thus prevents the lipoplexes from being cleared by the reticuloendothelial system. Problematically, this stabilization of lipoplexes simultaneously leads to reduced transfer efficiencies compared to non-PEGylated complexes. However, this reduction in transfer efficiency can be used to advantage since additional modification of PEGylated lipoplexes with functional groups enables improved selective transfer into target cells. Cancer cells overexpress folate receptors because of a significantly increased need of folate due to high cell proliferation rates. Thus, additional folate functionalization of PEGylated lipoplexes improves uptake into cancer cells. We demonstrate herein that NHS coupling chemistries can be used to modify two commercially available transfection reagents (Fuse-It-DNA and Lipofectamine® 3000) with NHS-PEG-folate for increased uptake of nucleic acids into cancer cells. Lipoplex characterization and functional analysis in cultures of cancer- and healthy cells clearly demonstrate that functionalization of PEGylated lipoplexes offers a promising method to generate efficient, stable and selective nucleic acid transfer systems.